The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2007
DOI: 10.1016/j.joca.2007.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Erratum to “Intermittent treatment of knee osteoarthritis with oral chondroitin sulfate: a one-year, randomized, double-blind, multicenter study versus placebo” [Osteoarthritis Cartilage 12 (2004) 269–276]

Abstract: The publisher regrets that in the above article the fourth author's name was spelt incorrectly. It is now represented correctly above as Florent de Vathaire.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
106
0
12

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(121 citation statements)
references
References 0 publications
3
106
0
12
Order By: Relevance
“…Only a few medications have been recognized by clinical trials as potentially influencing the course of OA beneficially. These include chondroitin sulfate (CS), [4][5][6][7] glucosamine, [8][9][10] diacerein, 11) doxycycline (an antibiotic belonging to the tetracycline family), 12) cyclooxygenase/5-lipoxygenase inhibitors, 13) and intra-articular injections of hyaluronic acid (HA). These approaches, however, have frequently produced insufficient benefit and excess risk of adverse effects.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few medications have been recognized by clinical trials as potentially influencing the course of OA beneficially. These include chondroitin sulfate (CS), [4][5][6][7] glucosamine, [8][9][10] diacerein, 11) doxycycline (an antibiotic belonging to the tetracycline family), 12) cyclooxygenase/5-lipoxygenase inhibitors, 13) and intra-articular injections of hyaluronic acid (HA). These approaches, however, have frequently produced insufficient benefit and excess risk of adverse effects.…”
mentioning
confidence: 99%
“…[25][26][27] Furthermore, the clinical efficacy of CS has been shown in improving OA joint function and in reducing cartilage destruction. [4][5][6][7][28][29][30] Singh et al recently conducted a review of randomized trials of OA interventions in the Cochrane Database of Systemic Reviews and concluded that CS may improve pain, that it probably improves QOL, and that it probably slows down narrowing of the joint space in patients with knee OA. 31) However, there have also been reports showing no effects of CS on pain or cartilage structure.…”
mentioning
confidence: 99%
“…ХС и глюкозамин с позиций доказательной медицины среди хондропротекторных средств имеют высшую сте-пень доказательности и достоверности результатов -категорию А, в связи с чем на их основе сегодня и произ-водят большинство хондропротекторов, применяющихся в мировой практике [23][24][25][26][27][28]. Поэтому применение глюко-замина и хондроитина сульфата является патогенетиче-ски обоснованным.…”
Section: ключевые слова: дорсалгия спондилоартроз структурно-модифициunclassified
“…Hyperuricemia leads to urate crystal formation and deposition in the joints thus initiating inflammatory response by triggering proinflammatory mediator production, such as reactive oxygen species (ROS), tumor necrosis factor-α (TNF-α), and interleukin-6 (IL-6) (Ferrari et al, 2016;Inokuchi et al, 2008;Choi et al, 2005). Medication prescribed to treat gout includes urate lowering agents and nonsteroidal anti-inflammatory drugs (NSAIDs) but these agents are associated with intolerances or adverse effects (Busso and So, 2010;Khanna et al, 2012;Liu-Bryan and Lioté, 2005;Umamaheswari et al, 2009;Wang et al, 2008;Wortman et al, 2010). Thus, the development of novel natural agents with therapeutic potential against gout would provide great clinical significance.…”
Section: Introductionmentioning
confidence: 99%
“…The use of these compounds have become increasingly popular for treatment of arthritis as both are safe and have no adverse effect (Uebelhart et al, 2004;Lovu et al, 2008;Volpi, 2009;Nagaoka, 2014). In our previous research, CS and glucosamine had been succesfully extracted from chicken feet cartilage using aqueous method.…”
Section: Introductionmentioning
confidence: 99%